HARDENING IN PSYCHOLOGY AS A FACTOR IN THE FORMATION OF PERSONAL STRESS RESILIENCE - Pulatov Djavdat Abdujabbarovich (Web of Journals Publishing, 2025)
The article examines the phenomenon of hardening from a psychological perspective as a systemic process of forming stress resilience and adaptive resources of personality. A theoretical analysis of the concepts of “hardening,” “stress resilience,” and “psychological resilience” is conducted based on classical and contemporary psychological theories [3; 6; 8]. The main psychological mechanisms of the influence of hardening factors are identified. The results of an empirical study aimed at identifying the relationship between the level of psychological hardening and indicators of stress resilience, anxiety, and self-regulation are presented. The obtained data confirm the significant role of hardening in the prevention of psycho-emotional disorders and in the development of adaptive behavior.
Keywords: Hardening, stress resilience, psychological adaptation, resilience, anxiety, self-regulation, empirical research.